5‐Fluorouracil preferentially sensitizes mutant KRAS non‐small cell lung carcinoma cells to TRAIL‐induced apoptosis. Issue 9 (20th June 2015) - Wang, Haizhen; Yang, Tao; Wu, Xiangwei
Abstract : Mutations in the KRAS gene are very common in non–small cell lung cancer (NSCLC), but effective therapies targeting KRAS have yet to be developed. Interest in tumor necrosis factor–related apoptosis‐inducing ligand (TRAIL), a potent inducer of cell death, has increased following the observation that TRAIL can selectively kill a wide variety of human cancer cells without killing normal cells both in vitro and in xenograft models. However, results from clinical trials of TRAIL‐based therapy are disappointingly modest at best and many have demonstrated a lack of therapeutic benefit. Current research has focused on selecting a subpopulation of cancer patients who may benefit from TRAIL‐based therapy and identifying best drugs to work with TRAIL. In the current study, we found that NSCLC cells with a KRAS mutation were highly sensitive to treatment with TRAIL and 5‐fluorouracil (5FU). Compared with other chemotherapeutic agents, 5FU displayed the highest synergy with TRAIL in inducing apoptosis in mutant KRAS NSCLC cells. We also found that, on a mechanistic level, 5FU preferentially repressed survivin expression and induced expression of TRAIL death receptor 5 to sensitize NSCLC cells to TRAIL. The combination of low‐dose 5FU and TRAIL strongly inhibited xenograft tumor growth in mice. Our results suggest that the combination of TRAIL and 5FU may be beneficial for patients with mutant KRAS NSCLC. Highlights: Chemotherapeutic drugs display different levels of synergy with TRAIL in NSCLC cells. 5FU has strongest synergy with TRAIL in inducing apoptosis in mutant KRAS NSCLC cells. The synergy between 5FU and TRAIL is mediated by 5FU‐induced repression of survivin and induction of DR5.